Association between Oxytocin Receptor Gene Polymorphisms and Self-Rated ‘Empathic Concern’ in Schizophrenia - Montag, Christiane (Public Library of Science, 2012)
The nonapeptide oxytocin (OXT) and its receptor (OXTR) have been implicated in social cognition, empathy, emotion and stress regulation in humans. Previous studies reported associations between OXT and OXTR genetic polymorphisms and risk for disorders characterized by impaired socio-emotional functioning, such as schizophrenia and autism. Here we investigate the influence of two single nucleotide polymorphisms (SNPs) within the OXTR gene on a measure of socio-emotional functioning in schizophrenic patients. OXTR SNPs that were previously investigated in other studies were genotyped in 145 patients diagnosed with schizophrenia according to DSM-IV and 145 healthy controls matched for age and gender. The Interpersonal Reactivity Index (IRI) was used to assess cognitive (‘perspective taking’), affective (‘empathic concern’) and self-related (‘personal distress’) dimensions of empathy. No group differences in genotype frequencies were observed. MANCOVA revealed a significant main (F [1,282] = 10.464; p<0.01) and interaction effect (genotype by diagnosis: F [1,282] = 4.329; p<0.05) of OXTR SNP rs2254298(A>GG) with ‘empathic concern’. Within the schizophrenia group, linear regression analysis determined OXTR rs2254298 genotype, PANSS negative and general symptom score, and age of disease onset as being significantly associated with ‘empathic concern’. OXTR rs2254298 significantly impacted PANSS general psychopathology scores. No associations were found for OXTR rs53576, IRI ‘perspective taking’ or ‘personal distress’ ratings. Our preliminary findings support hypotheses about an involvement of OXTR rs2254298 in emotional empathy in schizophrenic and healthy individuals, warranting independent replication.